2021
DOI: 10.21203/rs.3.rs-1120936/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared Responsibility for Carbon Emission Based on Embodied Carbon Emission in China-US Trade

Abstract: Traditional Production-Based Accounting (PBA) principle does not consider the embodied carbon emissions in export and import trade. A multiregional input-output (MRIO) model is constructed to estimate the embodied carbon dioxide emissions of 41 countries and regions worldwide, based on the PBA and shared responsibility approach in this paper. The results indicate that the embodied carbon emissions in 2018 in China's export trade were 1326.1 million tons higher than that of import trade. Through the empirical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Published by Francis Academic Press, UK -183-for a large proportion [5]. Moreover, the trade of agricultural products and food and other consumer goods is gradually increasing.…”
Section: Overview Of Sino-hungarian Tradementioning
confidence: 99%
“…Published by Francis Academic Press, UK -183-for a large proportion [5]. Moreover, the trade of agricultural products and food and other consumer goods is gradually increasing.…”
Section: Overview Of Sino-hungarian Tradementioning
confidence: 99%
“…Qiao et al (Qiao et al, 2018) measured the embodied carbon in trade of total and segmented industries between China and the other BRICS from 1992 to 2013, using the Eora database and the Tapio decoupling model to investigate the relationships between trade development and carbon emissions. Zhao (Zhao, 2015), Guo (Guo, 2017), Zhang (Zhang, 2017), and Qiu (Qiu, 2018) measured and compared The BRICS' foreign trade embodied carbon based on the input-output model, studied the influencing factors of the BRICS' trade embodied carbon by using structural decomposition method and econometric model, and predicted the BRICS' import and export embodied carbon from 2015 to 2020 by using ARIMA model. Through literature review, it can be found that multi regional input-output model has been widely used in the field of trade embodied carbon measurement.…”
Section: Research On Embodied Carbon In Tradementioning
confidence: 99%